Making it Work: Aesthetics and Affect in Dave Eggers’s What is the What - Geertsma, Anke (Academic Quarter | Akademisk kvarter, 2012)
This article explores the role of aesthetics and affect in the broader human rights claim that Dave Eggers’s" What is the What: The Autobiography of Valentino Achak Deng, a Novel" (2006) wants to make. The book describes the life of this Sudanese “Lost Boy” who has to flee his nation’s second civil war, spending decades in refugee camps in Ethiopia and Kenya before being brought to the U.S. The article considers "What is the What" as a cultural translation of a specific, local human rights violation into the dominant, Western discourse of human rights. One of the article’s conclusions is that “human rights work is, at its heart, a matter of storytelling”.